Efektivitas Penyidikan Tindak Pidana Narkoba di Wilayah Hukum Kepolisian Resor Musi Rawas - Setiawan, Eko; Idi, Abdullah; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
The purpose of this study is to analyze the Effectiveness of Drug Investigations in the Musi Rawas Resort Police Jurisdiction. The method used is a qualitative descriptive analysis technique. The results of the study revealed that the Investigation of Drug Crimes in the Musi Rawas Resort Police Jurisdiction has been effective. This can be seen based on the Effectiveness of Drug Crime Investigations in the Musi Rawas Resort Police Jurisdiction which includes the dimensions and indicators used are: Achievement of Objectives (Stages of the Drug Crime Investigation process, Targets of Drug Crime Investigation); Integration (Ability to disseminate information about Drug Crimes, Development of consensus with various parties who have other interests (stakeholders), Communication related to coordination with BNN institutions and to the community regarding Drug Crimes; and Adaptation (The process of determining competent investigators against drug crimes, The process of investigation based on legally established rules and procedures) all of which have been implemented effectively. It is necessary to optimize the handling of drug crimes, especially juvenile delinquency or increase supervision from law enforcement officials in dealing with drug crimes; It is necessary to optimize socialization and counseling about the dangers of drugs in society; and Increase community participation to prevent drug abuse in the Musi Rawas Resort Police area.